An ethic of indulgence? Alcohol, Ultimate Frisbee and calculated hedonism. (August 2016) - Crocket, Hamish
In this article, I use Featherstone's concept of calculated hedonism to analyse consumption of alcohol amongst Ultimate Frisbee players. Drawing on a multi-year ethnographic project, I examine Ultimate players' reasons for drinking and contextualize this drinking within Ultimate's broader lifestyle. This examination and contextualization contributes to a growing body of literature that goes beyond the dominant perspectives on sport-related drinking through its conceptualization of consumptive pleasures in the formation of player identity and relationships between players.